Analysis of meteorology–chemistry interactions during air pollution episodes using online coupled models within AQMEII phase-2. (August 2015) - Kong, Xin; Forkel, Renate; Sokhi, Ranjeet S.; Suppan, Peter; Baklanov, Alexander; Gauss, Michael; Brunner, Dominik; Barò, Rocìo; Balzarini, Alessandra; Chemel, Charles; Curci, Gabriele; Jiménez-Guerrero, Pedro; et al.
Abstract: This study reviews the top ranked meteorology and chemistry interactions in online coupled models recommended by an experts' survey conducted in COST Action EuMetChem and examines the sensitivity of those interactions during two pollution episodes: the Russian forest fires 25 Jul–15 Aug 2010 and a Saharan dust transport event from 1 Oct to 31 Oct 2010 as a part of the AQMEII phase-2 exercise. Three WRF-Chem model simulations were performed for the forest fire case for a baseline without any aerosol feedback on meteorology, a simulation with aerosol direct effects only and a simulation including both direct and indirect effects. For the dust case study, eight WRF-Chem and one WRF-CMAQ simulations were selected from the set of simulations conducted in the framework of AQMEII. Of these two simulations considered no feedbacks, two included direct effects only and five simulations included both direct and indirect effects. The results from both episodes demonstrate that it is important to include the meteorology and chemistry interactions in online-coupled models. Model evaluations using routine observations collected in AQMEII phase-2 and observations from a station in Moscow show that for the fire case the simulation including only aerosol direct effects has better performance than the simulations with no aerosol feedbacks or including both direct and indirect effects. The normalized mean biases are significantly reduced by 10–20% for PM10 when including aerosol direct effects. The analysis for the dust case confirms that models perform better when including aerosol direct effects, but worse when including both aerosol direct and indirect effects, which suggests that the representation of aerosol indirect effects needs to be improved in the model. Highlights: Aerosol feedbacks during two pollution episodes were examined. Eight WRF-Chem and one WRF-CMAQ simulations performed in AQMEII phase-2. The simulations including aerosol direct effects only performed better. The representation of aerosol indirect effects in the model needs to be improved.